The Development Of Learning Media For Mobile Learning Application The Language And Automata Theory On Finite State Automata (FSA) And Deterministic Finite Automata (DFA) Material Use Adobe Air for Android - Maulana Muhamad Sulaiman; Romi Andrianto; Muhamad Arief Yulianto (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2020)
The language and automata theory are which required course must implemented by college student in informatic engineering study program. In this course, there are finite state automata (FSA) and deterministic finite automata (DFA) which are important materials in language and automata theory. This material requires more understanding of mathematical logic from students to determine an input which can be accepted or rejected in an abstract machine system. The assist studentsÂ to understand the material, it is need to develop the learning media for mobile learning applications for languageÂ and automata theory on finite state automata (FSA) and deterministic finite automata (DFA) based on android as an evaluation of learning media for students. And the development of this learning media use the ADDIE development model (analysis, design, development, implementation, evaluation) toÂ design language and automata theory applications learning so can be support the learning process for students and then assist lecturer to explain the material more dynamic and applicative.